LiFi-based smart systems for industrial monitoring. (5th March 2021) - Prabakaran, N.; Naresh, K.; Kannadasan, R.; Sainikhil, K.
Light fidelity (Li-Fi) is an unfolding technology which can be used to transfer data through light. It is a complete transformation to the world of wireless data transfer. Harald Haas from the University of Edinburgh, UK termed and introduced light fidelity to world through the global talk show in which he demonstrated of a Li-Fi prototype at the TED Global Conference in Edinburgh on 12 July 2011. Challenging the pre-existing data transfer model namely the wireless fidelity (Wi-Fi) on various parameters such as speed, safety, reliability eco-friendliness and efficiency. The light emitting diode in a Li-Fi system is the source of data transfer utilising visible light as medium of communication. This can provide greater download capacity in comparison to the existing wired or wireless networks due to higher bandwidth of light. With such high potential every electronic day to day use commodity that has role of light over it can be thought of to be used as an internet accesses point. Since it cannot penetrate through walls, they have short range but are highly secure in the confinement of the surrounding in comparison to Wi-Fi and overcome the radio frequency bandwidth availability issues in the near future.